Budaya dan Spirit Ekonomi: Studi Etos Kerja Masyarakat Toraja di Kecamatan Biring Kanaya Kota Makassar - Anastasia Nely Balaba; Mr. Najamuddin; St. Junaeda (Rayhan Intermedia, 2022)
This study aims to examine the existence of Toraja culture in the Toraja overseas community and the impact of Toraja culture on the economic spirit and work ethic of the Toraja people in Biring Kanaya District. Finding out and answering: 1) Cultural spirit in building the work ethic of the Toraja people in Biring Kanaya District; 2) The economic spirit of the Toraja people in Biringkanaya District; and 3) The impact of Toraja culture on the economic spirit and work ethic of the Toraja people in Biring Kanaya District. This research is descriptive qualitative. The selected informants are indigenous Toraja residents who are currently living in Biring Kanaya District, Makassar City. Researchers collect data through interviews and documentation. The results of the study show that the work ethic of the Toraja people, which is based on the desire to perform and participate in the Solo Rambu Ceremony, gives the view that work is able to provide encouragement in shaping a quality life and forming a work ethic. The motivation of the Toraja people in forming an economic spirit is the existence of the Solo Sign Ceremony which in its implementation requires a large enough cost so that the Toraja people try to find jobs that can improve their economy. Education is the driving force for the Toraja people to migrate. The resulting impact is to make culture an excuse to work hard, which then becomes the economic spirit of the overseas community, and forms a good work ethic.